Corporate Social Responsibility Reporting Affecting Earning Management and Operational Performance of Companies Listed in the Stock Exchange of Thailand - et. al., Phanthip Yangklan, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The objectives of the research on the corporate social responsibility reporting affecting earning management and operational performance of companies listed in the Stock Exchange of Thailand were to study the effects of corporate social responsibility reporting on the earning management and operational performance of companies listed in the Stock Exchange of Thailand and to study the effects of the earning management on the operational performance of companies listed in the Stock Exchange of Thailand. The population used in this study was 471 companies listed in the Stock Exchange of Thailand. The data was completely collected for 314 companies. The independent variables was the corporate social responsibility reporting in 5 aspects consisting of environment, energy, employees or workers, community, and product responsibility. The variables were earning management based on the Modified Jones Model and the Yoon Model. The operational performance was measured with the Economic Value Added (EVA). The descriptive statistics and inferential statistics were used in the analysis including the path analysis and model analysis to verify the model. The hypothesis was tested using the significance level of 0.05.The research results revealed that corporate social responsibility reporting in the environmental and energy aspects had significant negative influences on the earning management based on the Modified Jones Model and the Yoon Model. The Modified Jones Model earning management had a significant negative influence with the performance of the Economic Value Added. The corporate social responsibility reporting in 5 areas had the significant positive influence on the operational performance of companies listed in the Stock Exchange of Thailand.